Internalization of Religious Character Values through Discussion Activities Ngopi Bengi at IPNU-IPPNU Tahunan Branch - Dhakiroh, Eilin; As`ad , Ali (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study aims to analyze the process of internalizing religious character values through ngopi bengi discussion activities at IPNU-IPPNU Ranting Tahunan. This research is the result of field research at IPNU-IPPNU Ranting Tahunan. This research was conducted using a qualitative approach and a qualitative descriptive method. The data collection techniques were carried out by observation of Ngopi Bengi Discussion activities, interviews with the chairman and members of IPNU IPPNU, and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results showed that the process of internalizing religious character values through Ngopi Bengi discussion activities in IPNU-IPPNU Ranting Tahunan could be one of the means of a religious organization to improve character values, responsibility, patience, discipline, caring, tolerance, and spirituality. Ngopi Bengi discussion activities are not only a means to deepen religious knowledge by discussing with the cleric, but also to shape participants' religious character values for the better through application in everyday life. With an approach based on spiritual, social, and competition education, this activity proves the relevance of religious character internalization methods in facing modern social challenges. Keywords: Character Value, Religious, religious discussion